Trust: A Concept Too Many - Timothy W. Guinnane (Yale University, Economic Growth Center, 2005)
Research on 'trust' now forms a prominent part of the research agenda in history and the social sciences. Although this research has generated useful insights, the idea of trust has been used so widely and loosely that it risks creating more confusion than clarity. This essay argues that to the extent that scholars have a clear idea of what trust actually means, the concept is, at least for economic questions, superfluous: the useful parts of the idea of trust are implicit in older notions of information and the ability to impose sanctions. I trust you in a transaction because of what I know about you, and because of what I can have done to you should you cheat me. This observation does not obviate what many scholars intend, which is to embed economic action within a framework that recognizes informal institutions and social ties. I illustrate the argument using three examples drawn from an area where trust has been seen as critical: credit for poor people.
Keywords: G2; N2; 330; Trust; Social Capital; Credit Cooperatives; Uniform Laws; Vertrauen; Social Capital; Genossenschaftsbank; Deutschland; Irland; USA